Joule-Thomson expansion, motion of particles and QPOs around Bardeen-AdS black hole immersed in a fluid of strings - Mustafa, G.; Javed, Faisal; Maurya, S. K.; Alkarni, Shalan; Donmez, Orhan; Cilli, Arzu; Gudekli, Ertan (ELSEVIER, 2024)
In this work, we investigate the dynamics of particles around a Bardeen AdS black hole immersed in a fluid of strings, focusing on how the black hole parameters affect particle motion. We observe the black hole's Joule-Thomson expansion and the impact of physical parameters on the cooling and heating zones. Using Joule- Thomson coefficients, we also discuss the stable and unstable configuration of the considered black hole for both cases. The stability of circular equatorial orbits is analyzed using the effective potential approach. We derive analytical expressions for the energy and angular momentum of these circular orbits as functions of the black hole parameters. We also explore the impact of these parameters on the innermost stable circular orbits and discuss the effective forces acting on the particles. In addition, we examine the epicyclic oscillations of particles near a stable equatorial orbits and calculate the corresponding oscillation frequencies as function of black hole parameters. The periastron frequency is also analyzed. Furthermore, we study particle collisions and the resulting center of mass-energy in the vicinity of the black hole. We show that the parameters of the model significantly influence particle motion. Lastly, we compare the particle dynamics around the Bardeen AdS black hole immersed in a fluid of strings with those around the Bardeen black hole and the Bardeen Reissner-Nordstr & ouml;m black hole.
Keywords: Circular orbits; Particle dynamics; Particle collision; Quasi-periodic oscillations; Black hole physics; DYNAMICS; STABILITY; MODELS; STAR; MASS; SPIN; Astronomy & Astrophysics